Incidence, risk factors and outcomes of acute kidney injury among COVID-19 patients: A systematic review of systematic reviews - Mallhi, Tauqeer Hussain; Khan, Yusra Habib; Alzarea, Abdulaziz Ibrahim; Khan, Faiz Ullah; Alotaibi, Nasser Hadal; Alanazi, Abdullah Salah; Butt, Muhammad Hammad; Alatawi, Ahmed D.; Salman, Muhammad; Alzarea, Sami I.; Almalki, Ziyad Saeed; Alghazi, Mansoor A.; et al. (Frontiers in Medicine, 2022)
The COVID-19 associated AKI (CAKI) has emerged as a potential intricacy during the management of patients. Navigating the rapidly growing body of scientific literature on CAKI is challenging, and ongoing critical appraisal of this complication is essential. This study aimed to summarize and critically appraise the systematic reviews (SRs) on CAKI to inform the healthcare provides about its prevalence, risk factors and outcomes. All the SRs were searched in major databases (PubMed, EMBASE, Web of Science) from inception date to December 2021. This study followed SR of SRs methodology, all the records were screened, extracted and subjected to quality assessment by AMSTAR-2. The extracted data were qualitatively synthesized and tabulated. This review protocol was registered in PROSPERO (CRD42022299444). Of 3833 records identified; 42 SRs were included in this overview. The quality appraisal of the studies showed that 17 SR were of low quality, while 8 moderate and 17 were of high-quality SRs. The incidence of CAKI ranged from 4.3% to 36.4% in overall COVID-19 patients, 36% to 50% in kidney transplant recipients, and up to 53% in severe or critical illness. Old age, male gender, cardiovascular disease, chronic kidney disease, diabetes mellitus and hypertension were frequently reported risk factors of CAKI. The need of renal replacement therapy (RRT) was up to 26.4% in overall COVID-19 patients, and 39% among those having CAKI. The occurrence of AKI was found independent predictor of death, where mortality rate among CAKI patients ranged from 50% to 93%. This overview of SRs underscores that CAKI occurs frequently among COVID-19 patients and associated with high mortality, need of RRT and adverse outcomes. However, the confidence of these results is moderate to low which warrants the need of more SRs having established methodological standards.